Glucose-Regulated Protein 78 Interacts with Zika Virus Envelope Protein and Contributes to a Productive Infection. (2020)
Zika virus (ZIKV; Flaviviridae) is a mosquito-borne flavivirus shown to cause fetal abnormalities collectively known as congenital Zika syndrome and Guillain-Barre syndrome in recent outbreaks. Currently, there is no specific treatment or vaccine available, and more effort is needed to identify cellular factors in the viral life cycle. Here, we investigated interactors of ZIKV envelope (E) protein by combining protein pull-down with mass spectrometry. We found that E interacts with the endoplasmic reticulum (ER) resident chaperone, glucose regulated protein 78 (GRP78). Although other flaviviruses are known to co-opt ER resident proteins, including GRP78, to enhance viral infectivity, the role ER proteins play during the ZIKV life cycle is yet to be elucidated. We showed that GRP78 levels increased during ZIKV infection and localised to sites coincident with ZIKV E staining. Depletion of GRP78 using specific siRNAs significantly reduced reporter-virus luciferase readings, viral protein synthesis, and viral titres. Additionally, GRP78 depletion reduced the ability of ZIKV to disrupt host cell translation and altered the localisation of viral replication factories, though there was no effect on viral RNA synthesis. In summary, we showed GRP78 is a vital host-factor during ZIKV infection, which may be involved in the coordination of viral replication factories.